Analisis Implementasi Kaidah Fikih LÄ á¸Œarar Wa LÄ á¸ŒirÄr dalam Kedokteran Modern pada Kasus Tindakan Operasi - Muhammad Nirwan Idris; Kurnaemi Anita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The relevance of the principles of fiqh in interpreting the law of a number of cases in the world of modern medicine has long been applied globally by classical and contemporary fiqh scholars. Advances in technology in the field of medicine have given rise to a number of controversial medical treatments and measures. For this reason, this study was carried out to describe the concept of fiqh la> darar wa la> dira>r in formulating shari'a law in medical disciplines and the correlation between the two, then implementing it based on the case examples described. This study uses qualitative analytic research with a phenomenological approach. The results of the study concluded that medical treatment that violates the shari'ah code of ethics and poses a danger and damage to the patient concerned can be included in the la> darar wa la> dira>r rules. Examples of cases such as hysterectomy carried out due to medical and emergency interests, are permitted as the application of the rules of al-darar yudfaâ€™ bi qadr al-imka>n. Then medical treatment is not carried out for reasons of treatment and emergency needs, such as changing parts of the body for beauty and trends, or taking actions that according to the medical there are dangers and negative effects that are greater than the benefits, then it can be included in the rules of ' darâ€™u al-mafÄsid muqaddam â€˜ala> jalbi al-masa>lih. In the case of autopsy and eugenic abortion are included in the rule of the law iza> taâ€™a>rada mafsadata>n ru>â€™iya aâ€™zamuhuma dararan bi irtika>bi akhaffihima>, for taking less harm should be done to avoid greater harm, and this is the most appropriate opinion on this issue.",